Evidence on yoga for health: A bibliometric analysis of systematic reviews - L.S. Wieland; H. Cramer; R. Lauche; A. Verstappen; E.A. Parker; K. Pilkington (Elsevier, 2021)
Objective: To support the research agenda in yoga for health by comprehensively identifying systematic reviews of yoga for health outcomes and conducting a bibliometric analysis to describe their publication characteristics and topic coverage. Methods: We searched 7 databases (MEDLINE/PubMed, Embase, PsycINFO, CINAHL, AMED, the Cochrane Database of Systematic Reviews, and PROSPERO) from their inception to November 2019 and 1 database (INDMED) from inception to January 2017. Two authors independently screened each record for inclusion and one author extracted publication characteristics and topics of included reviews. Results: We retrieved 2710 records and included 322 systematic reviews. 157 reviews were exclusively on yoga, and 165 were on yoga as one of a larger class of interventions (e.g., exercise). Most reviews were published in 2012 or later (260/322; 81 %). First/corresponding authors were from 32 different countries; three-quarters were from the USA, Germany, China, Australia, the UK or Canada (240/322; 75 %). Reviews were most frequently published in speciality journals (161/322; 50 %) complementary medicine journals (66/322; 20 %) or systematic review journals (59/322; 18 %). Almost all were present in MEDLINE (296/322; 92 %). Reviews were most often funded by government or non-profits (134/322; 42 %), unfunded (74/322; 23 %), or not explicit about funding (111/322; 34 %). Common health topics were psychiatric/cognitive (n = 56), cancer (n = 39) and musculoskeletal conditions (n = 36). Multiple reviews covered similar topics, particularly depression/anxiety (n = 18), breast cancer (n = 21), and low back pain (n = 16). Conclusions: Further research should explore the overall quality of reporting and conduct of systematic reviews of yoga, the direction and certainty of specific conclusions, and duplication or gaps in review coverage of topics.